Islamic Work Ethic: The Role of Religious Principles on Working Performance in Higher Education - Noer, Muli Umiaty (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The study aims to investigate the influences of the Islamic work ethic to increase the working motivation of academics at the Academy of Foreign Languages, Universitas Muslim Indonesia. It employs quantitative research by applying an explanatory research model. Using saturation sampling involved all the lecturers and academic staff assigned to the Foreign Language Academy at the Universitas Muslim Indonesia, Makassar, Indonesia. The target participants in this study were 34 people. The data was collected using a questionnaire compiled based on Islamic Working Ethic, Islamic Working Motivation, and Working Performance variables. The results showed that the Islamic working ethic has a favorable and substantial impact on academics' working performance in learning. Based on the aqidah tauhid, the state suggests that all indications of work ethic influence enhancing job performance so that lecturers get His joy. The work ethic with an Al-Mujahadah attitude or optimal hard work will motivate the academics to work harder, thereby improving their performance.